Efficacy of school-based intervention programs in reducing overweight: A randomized trial - Marsigliante, Santo; Ciardo, Vito; Di Maglie, Antonio; My, Giulia; Muscella, Antonella (Frontiers in Nutrition, 2022)
Childhood obesity represents a serious public health problem and this study evaluates the effectiveness of a 6-month educational intervention on lifestyle, nutrient adequacy, and diet quality in the school setting in improving the knowledge and behavior of primary school children regarding correct eating habits. The strategy was implemented over a 6-month period and participants were randomly assigned to either the intervention group (n = 200) or the non-intervention group (control group, n = 197). Participants had a mean body mass index of 18.3 ± 2.7 kg/m2 and its variation in the intervention group (−2.7 ± 0.5 kg/m2) was significantly different from that in the control group (3.41 ± 0.8 kg/m2). In the experimental group, there were significant differences between the proportion of children who were overweight, underweight, normal weight, or obese before and after intervention (p < 0.05). The best results were seen in the female sex, and after the intervention, there were no more girls with obesity. Furthermore, there were significant waist circumference decrement effects in the intervention group compared to the control group (p < 0.05). Finally, many of the participating children acquired healthy eating habits. Therefore, the quantitative results obtained suggest that a school intervention program represents an effective strategy to prevent and improve the problem of childhood overweight and obesity.